CORPORATE GOVERNANCE AND EARNINGS PERSISTENCE OF LISTED NIGERIAN FIRMS - Abogun, Segun; Orilonise, Mubarak; Dauda, ISAH; KASUM, Abubakar Sadiq (Universidad Francisco de Paula Santander, 2024)
Information about the performance of firms is very important to investors for making investment decision. However, investors of firms in developing economies particularly in Nigeria are faced with the problem of access to relevant and reliable information. In view of this, this study examines the effect corporate governance has on earnings persistence of Nigerian listed firms. This research employed the explanatory research design. It generated sampling frame for companies that are listed in 2002 and continues to be listed up to 2021, the entire 51 companies were used, using census sampling technique. Secondary data was employed for this study, extracted from the companies’ audited annual reports. The data obtained were analyzed using dynamic panel regression model. Findings from this study show that: (i) previous year earnings significantly influence current year earnings. (ii) Corporate governance has significant negative influence on the earnings of Nigeria listed firms. (iii) Current year earnings are significantly influenced by the interaction between corporate governance and the past year’s earnings. The study recommends the need for Nigeria listed firms to focus on improving their governance structures through appointing independent directors to the board, establishing effective internal control systems, and ensuring that executive compensation is aligned with long-term performance.